The Influence of Pharmacogenetic Variants in HIV/Tuberculosis Coinfected Patients in Uganda in the SOUTH Study - Calcagno, Andrea; Cusato, Jessica; Sekaggya-Wiltshire, Christine; von Braun, Amrei; Motta, Ilaria; Turyasingura, Grace; Castelnuovo, Barbara; Fehr, Jan; Di Perri, Giovanni; Lamorde, Mohammed (Clinical pharmacology and therapeutics, 2019)
Unsatisfactory treatment outcomes have been reported in patients coinfected with HIV/tuberculosis (TB). The aim of this study was to assess the influence of single-nucleotide polymorphisms (SNPs) in genes encoding for proteins involved in antitubercular drug disposition or effect. A pharmacogenetic study was conducted in Kampala, Uganda, where all analysis was performed. The impact of SNPs on antitubercular drug exposure, adverse events, and treatment outcomes was evaluated in patients coinfected with HIV/TB receiving treatments for both conditions. In 221 participants, N-acetyltransferase 2 (NAT2; rs1799930), solute carrier organic anion transporter family member 1B1 (SLCO1B1; rs4149032), and pregnane X receptor (PXR; rs2472677) variants affected isoniazid exposure in multivariate analysis. Most patients were deemed cured (163; 73.8%), yet PXR 63396TT carriers had a higher probability of death (P = 0.007) and of worsening peripheral neuropathy (P = 0.018). In this exploratory study in Ugandan patients coinfected with HIV/TB, genetic variants in PXR, SLCO1B1, and NAT2 were moderately associated with isoniazid exposure, whereas PXR 63396TT carriers showed worse outcomes.